Analyzing urban green space inequalities in Isparta, Turkey - GÜL, Atila; Dinç, Gizem; Aydemir, Çağla (TeMA - Journal of Land Use, Mobility and Environment, 2024)
Cities defined by population size, heterogeneity, and dynamic change face historical and contemporary inequalities. The United Development Goals underline the urgency of addressing urban inequality, which has been exacerbated by the COVID-19 pandemic. Urban open and green spaces emerge as important elements for social well-being and affect social, cultural, and psychological aspects. Despite their importance, inequalities in the distribution, quantity, and function of these areas persist. Standards advocating a minimum of 9 m2 of green area per person and accessibility become an important component. However, global data reveals that distribution is inadequate; Only 37.8% of neighborhoods in the city are conveniently located near open public spaces. This study examines the distribution, size, and accessibility of urban green spaces, focusing on Isparta. Unequal distributions were detected in terms of the area covered by green spaces in the neighborhoods, their accessibility, and green spaces per capita. The findings reveal the need for measures to correct urban inequality in planning, design, and management policies, which will contribute to the creation of sustainable and livable cities.